Musculoskeletal complaints in caregivers of the elderly in the municipality of Ecoporanga - ES (International Seven Journal of Health Research, 2023)
Introduction: The caregiver of the elderly is the person responsible for taking care of the elderly, participating in their routine and taking care of their physical, emotional and social needs. The caregiver donates his/her time to care by working most of the day in positions that are uncomfortable and harmful to the musculoskeletal system, leading to the development of occupational diseases. Objective: To analyze musculoskeletal complaints in caregivers of the elderly. Methodology: This is a quantitative, exploratory and descriptive research carried out through the application of the Nordic Musculoskeletal Symptom Questionnaire composed of 18 structured questions. The sample consisted of 14 Caregivers of the Elderly in the Municipality of Ecoporanga-ES. The questionnaires were applied from May 23 to 24, 2023. Of the inclusion criteria, caregivers who agreed to participate in the research were observed. Results: It was noted that the questionnaire was answered by 57.14% of women and 42.85% of men aged between twenty-one and fifty-nine years, 71.41% of the interviewees felt cervical discomfort and 85.69% felt discomfort in the lumbar stomach. Conclusion: It was concluded that all caregivers complain of at least one type of musculoskeletal disorder associated with the activity of caregiving, and that despite the pain, 85.71% never took sick leave and no caregiver underwent surgery to treat the pain.